Case report: Intraventricular tumor removal using transcallosal approach and follow-up in three dogs - Lehner, László; Czeibert, Kálmán; Csébi, Péter; Diószegi, Kristóf; Nagy, Gábor (Frontiers in Veterinary Science, 2023)
This case series describes the surgical removal of lateral ventricular tumors using a transcallosal approach, long-term follow-up, and magnetic resonance imaging (MRI) results of 3 dogs. Two tumors were benign choroid plexus tumors (CPT). One was a grade 2 astrocytoma. Complete tumor removal was achieved using the transcallosal approach. All dogs had ventriculomegaly which remained static or progressed during the follow-up period. All dogs had epileptic seizures before the surgical procedure which persisted despite tumor removal. One dog with CPT was alive after 3 years and 5 months and had minor focal seizures every 3–4 months. No other clinical signs were observed. The second dog with CPT was neurologically free for 17 months after the surgical procedure but died due to acute-onset therapy-resistant generalized epileptic seizures. The third dog with intraventricular astrocytoma experienced epileptic seizures 2 and 4 months after the surgical procedure. The second event was therapy-resistant which led to death.